Growth and health performance of African catfish Clarias gariepinus (Burchell 1822) juvenile fed with graded levels of biofloc meal. (23rd April 2019) - Ekasari, Julie; Setiawati, Rovi; Ritonga, Fitria Rahmadani; Setiawati, Mia; Suprayudi, Muhammad Agus
Abstract: The objective of the study was to evaluate the utilization of biofloc meal as a feed ingredient in enhancing the growth and health status of African catfish ( Clarias gariepinus ) juvenile. The study consisted of two experiments, that is digestibility and growth experiments. The digestibility of two biofloc meals produced with two different carbon sources, that is tapioca and molasses, were assessed in the digestibility experiment. Whereas the effect of four dietary treatments with different levels of biofloc meal, that is 0%, 5%, 10% and 20%, on the fish growth performance, feed utilization, immuno‐haematological response, antioxidant status and robustness against environmental stress were evaluated in the growth experiment. The results showed that the digestibility of dry matter, protein, lipid and phosphorus of biofloc grown using molasses as the carbon source were remarkably higher than that grown using tapioca ( p  < 0.05). The inclusion of biofloc meal in the diets at 10% and 20% resulted in higher feed intake, fish growth and final biomass and protein efficiency ratio, and lower feed conversion ratio ( p  < 0.05). Furthermore, the red blood cells counts, phagocytic, lysozyme activities and antioxidative capacity were significantly enhanced in the fish provided with diet containing 20% biofloc meal ( p  < 0.05).The fish survival following salinity stress test was higher in the treatments with biofloc meal at 10% and 20% inclusion levels. In conclusion, dietary inclusion of biofloc meal could improve the growth performance and health status of African catfish juvenile and an inclusion level of 20% could be recommended.